(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Cystitis is an inflammation of the urinary bladder mucosa, commonly caused by infections, chemical irritants, trauma, or autoimmune conditions. In this condition, significant histological changes occur in the bladder wall. These include hyperemia (dilation of blood vessels), edema, and infiltration by inflammatory cells such as lymphocytes, neutrophils, and plasma cells. The epithelial layer often shows degenerative and dystrophic changes. In severe cases, purulent necrosis, inflammatory infiltrates, microabscesses, and increased fibroblast activity leading to connective tissue proliferation can be observed. In chronic cystitis, the bladder wall becomes thickened, with fibrous connective tissue growth in the submucosal layer and persistent lymphoid infiltration.